(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The article analyzes the composition of ergonims from the semantic point of view and the structural types of ergonims. All object names can be divided into real and symbolic names.